Situation Report: Hungary, 3 January 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The HSWP Riddle: How to Create "Party Democracy" / by Edith Markos Hungarian Party Theorist Defends Political and Economic Reforms / by Slobodan Stankovic Hungary's Oil and Natural Gas Reserves: Going after Every Last Drop / by Steven Koppany Coal Mining Industry in Dire Straits / by Alfred Reisch New Organizations to Help Communist Youth League / by Edith Markos Hungarian-Bavarian Beer: An East-West Misalliance? / by Eva Lengyel Party Daily Gets New Editor in Chief / by Alfred Reisch Defense Minister Dies / by Alfred Reisch Political Officer Appointed as New Defense Minister / by Alfred Reisch